2021
DOI: 10.3390/ijms22105325
|View full text |Cite
|
Sign up to set email alerts
|

A Keratin 7 and E-Cadherin Signature Is Highly Predictive of Tubo-Ovarian High-Grade Serous Carcinoma Prognosis

Abstract: During tubo-ovarian high-grade serous carcinoma (HGSC) progression, tumoral cells undergo phenotypic changes in their epithelial marker profiles, which are essential for dissemination processes. Here, we set out to determine whether standard epithelial markers can predict HGSC patient prognosis. Levels of E-CADH, KRT7, KRT18, KRT19 were quantified in 18 HGSC cell lines by Western blot and in a Discovery cohort tissue microarray (TMA) (n = 101 patients) using immunofluorescence. E-CADH and KRT7 levels were subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Antibody specificity was validated and the baseline expression of KRT7 in prostatic cell lines with different species of antibodies (mouse OV-TL 12/30 and rabbit SP52) was determined by Western blot assay on whole-cell extracts ( Supplementary Figure S1A ). Both mouse and rabbit antibodies showed specific and similar bands around the expected 51 kDa molecular weight ( Supplementary Figure S2 ), as previously described [ 18 ]. It was noted that the KRT7 protein level was higher in castration-resistant PC cell lines (DU145, PC3) and non-malignant prostate cell lines (PZ-HPV-7 and RWPE-1) when compared to hormone-sensitive PC cell lines (22Rv1 and LNCaP).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Antibody specificity was validated and the baseline expression of KRT7 in prostatic cell lines with different species of antibodies (mouse OV-TL 12/30 and rabbit SP52) was determined by Western blot assay on whole-cell extracts ( Supplementary Figure S1A ). Both mouse and rabbit antibodies showed specific and similar bands around the expected 51 kDa molecular weight ( Supplementary Figure S2 ), as previously described [ 18 ]. It was noted that the KRT7 protein level was higher in castration-resistant PC cell lines (DU145, PC3) and non-malignant prostate cell lines (PZ-HPV-7 and RWPE-1) when compared to hormone-sensitive PC cell lines (22Rv1 and LNCaP).…”
Section: Resultssupporting
confidence: 79%
“…No previous study had identified KRT7 as a putative prognostic biomarker in PC, and only few conflictual data described an association between the Gleason score and percentage of KRT7 positivity [ 20 , 52 ]. However, its overexpression alone or in combination (E-cadherin) in several other cancer types has been reported to predict a poor prognosis [ 15 , 16 , 17 , 18 ]. On the other hand, high KRT7 expression was associated with a better prognosis in renal cell carcinoma, as an example [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A closer examination of the clinicopathological characteristics of these specimens found these to be from patients with high-risk features such as either recurrences or PNI. PCA loadings show that the genes exerting the largest effects include MMP1 and MMP10 , KRT7 , and KRT19 ( Figure 3C ), high levels of which in other cancers have been associated with unfavorable prognosis ( 64 ). Another example is SPP1 , which encodes a stromal cell ligand shown to interact with integrin receptors encoded by ITGB1 and ITGA5 , which are both enriched on TSKs ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the overall survival (OS) effect of hub genes in HNSC was estimated by calculating the log−rank p−value and the hazard ratio (HR). Patients were divided into high (higher than the 75 th percentile) and low (lower than the 25 th percentile) expression groups based on the normalized expression level of the selected gene across all HNSC patients in the database (23). Since there is no OSCC category in both GEPIA and TCGA databases, and OSCC accounts for ~95% of HNSC, we chose HNSC as the category for these validation analyses.…”
Section: Validation Of Hub Genesmentioning
confidence: 99%